Why does health literacy matter, and for whom? Explaining the differentiating impact of health literacy on vaccine attitudes - Lubej, Maruša; Kirbiš, Andrej (Frontiers in Psychology, 2025)
IntroductionVaccination has substantially reduced the spread and severity of infectious diseases. Despite its efficacy, vaccine hesitancy remains a global challenge, often linked to inadequate health literacy and unfavorable vaccine attitudes. Understanding the mechanisms through which health literacy influences vaccine-related attitudes is crucial because it could inform policy interventions aimed at fostering more favorable vaccine attitudes.MethodThe present cross-sectional study of Slovenian adults (n = 3,360) examined the impact of health literacy on vaccine attitudes, focusing on the mediating role of beliefs in vaccine myths and the moderating effects of gender, education, economic status, healthcare training, and self-rated health.ResultsUsing mediation and moderated mediation models, we found that health literacy positively influences vaccine attitudes both directly and indirectly by reducing beliefs in myths. The relationship between health literacy and vaccine attitudes is moderated by healthcare training, with stronger positive effect among individuals with such training. Additionally, the negative effect of health literacy on beliefs in myths is stronger among individuals with higher education.DiscussionOur findings indicate that broader educational inequalities should be addressed to ensure that the positive effect of health literacy on vaccine attitudes is distributed more equitably across groups with different educational levels and fields of expertise.